The Degree of Strategies Usage for Learning Arabic Vocabulary by Foreign Learners of Arabic and their opinions about these Strategies Usage (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
This study aims at identifying the degree of Strategies Usage for learning Arabic vocabulary by foreign learners of Arabic at Ferdowsi University in Mashhad in Iran. The study sample consisted of (136) foreign learners of Arabic. To achieve the study goals, the researcher designed a questionnaire about the The Degree of Strategies Usage for learning Arabic vocabulary by foreign learners of Arabic, after verifying its validity and reliability. The study yielded the following results: • Arabic learners use a variety of strategies.• There was a high degree of usage of  different vocabulary learning strategies, with the strategy of using a dictionary in the first place, and the strategy of guessing meaning from context last in rank.• The results also show that learners are aware of the importance of learning vocabulary, using certain techniques, and employing different strategies for mastering lexis and processing words through repetition and memorization to acquire them, using the item in different contexts as in reading and writing, and emphasizing the importance of meaning and derivational relations in learning vocabulary. هدفَ البحث إلى تحديد درجة استعمال استراتيجيات تعلم المفردات العربية لدى متعلمي اللغة العربية الناطقين بغيرها في جامعة فردوسي بمدينة مشهد الإيرانية، وتعرف آراء هؤلاء المتعلمين في استعمال استراتيجيات تعلم المفردات. وقد تكوّنت العيّنة من (136) متعلماً ومُتعلمة من متعلمي اللغة العربية الذين يدرسونها لغة أجنبية في جامعة فردوسي بمدينة مشهد الإيرانية. ولتحقيق أهداف البحث أعدت الباحثة استبانة درجة استعمال استراتيجيات تعلم المفردات العربية لدى متعلمي اللغة العربية الناطقين بغيرها وطبقتها بعد التحقق من صدقها وثباتها. وقد أشارت النتائج إلى ما يأتي: 1. تنوع الاستراتيجيات التي يستعملها المتعلمون لتعلم المفردات العربية. 2. وجود درجة استعمال مرتفعة لاستراتيجيات تعلم المفردات مجتمعة، وقد تصدرت استراتيجية "استعمال المعجم" هذه الاستراتيجيات بدرجة استعمال مرتفعة. أمَّا أقل الاستراتيجيات استعمالاً من قبل المتعلمين فقد كانت استراتيجيات (تخمين المعنى من السياق) والتي حصلت على أقل المتوسطات، ودرجة استعمال منخفضة. 3. كما بينت النتائج أن لدى المتعلمين وعياً بأهمية استعمال استراتيجيات تعلم المفردات، وضرورة استعمال تقنيات وتوظيف أساليب واستراتيجيات مختلفة في تعلم المفردات، ومعالجتها، بما في ذلك التكرار والحفظ، واستعمال الكلمة في سياقات متنوعة، وفي القراءة والكتابة، والاهتمام بِدَور العلاقات المعنوية والاشتقاقية في تعلّم الكلمات.